Interaksi Komunikasi Hoax Di Media Sosial Serta Antisipasinya - Muhammad Salim Albana; Alif Dava Mahesa; Indriani Putri; Noerma Kurnia Fajarwati (STIKes Ibnu Sina Ajibarang, 2024)
This study aims to get an overview of the interaction of hoax communication on social media and how to anticipate it. This study uses a qualitative method with a case study approach, by comparing three different hoax cases that are popular in Indonesian society, namely hoaxes about the government of President Jokowi, hoaxes about the Governor of DKI Jakarta Ahok, and hoaxes about the Covid-19 pandemic. The data used in this study come from various sources, such as social media, mass media, reports, documents, or interviews. The collected data were then analyzed using content analysis, discourse analysis, or narrative analysis techniques, according to the type and nature of the data. The results of this study show that the interaction of hoax communication on social media is a complex, dynamic, and multidimensional communication process, involving various parties, factors, and impacts. This study also shows that the anticipation of hoaxes on social media is a comprehensive, collaborative, and coordinated effort, involving various parties, approaches, and strategies. This study contributes to the development of communication science, benefits for communication practitioners, and input for related parties, in dealing with and overcoming hoaxes on social media.